(untitled) (KASBIT Business Journal, 2024)
Since the beginning of the 1990s, Pakistan’s foreign reserves have increased extremely quickly. The impact of Pakistan’s foreign indebtedness on currency rates has yet to get much focus in the scientific literature despite the media spotlight accompanying those obligations. This research examines the impact and relation of foreign debt and foreign exchange reserves with the monetary rate in Pakistan. The data in this research is taken for 15 years (2008-2022). Covariance suggests a strong positive relationship between foreign debt and the monetary rate and a negative correlation between foreign exchange reserves and the monetary rate. Ordinary Least Square (OLS) indicates that foreign debt has a negative significant impact on the monetary rate in Pakistan (p<0.05). At the same time, foreign exchange reserves have a positive significant impact on the monetary rate in Pakistan (p<0.05). In the future, the government should not rely on debt more and more as it affects the economy negatively because of the monetary rate increase. Apart from that, the State Bank should also focus on fewer reserves because it reduces the interest rate, which can cause more inflation in the economy of Pakistan.